Cangaceiros e devotos : religiosidade no movimento do cangaço (Nordeste brasileiro, 1900-1940) - Tavares, Eraldo Ribeiro (2014)
Known as a criminal, man of no mercy, a blood kille , monster and even as the own encarnation of the devil, Virgulino Ferreira da Silva, marked the History of the northeast region of Brazil and even the brasilian one, with his long twenty runaway years and crimes through the northeast sertão region of Brazil. This work shows what few people know and just a few researchers dedicated themselves to unveil: The Cangaceiro Lampião, whom altogether with the other members of his group, developed the other side of the existence as a being the issue of his religiosity. As most of the northeast people who practise the so called popular catholicism, Lampião, kept his relationship with angels and saintmen, he prayed every day and had his beliefs in ocult forces and in dreams. He never tried to get away with the rules on which he was upbrought since he was a kid, which were imposed by his mother and grandmother, who were the responsilble ones for his religious education. He was devoted for some saintmen, in special Hail Mary of Conception (Nossa Senhora da Conceição). He had the habit of saying last minute catholic masses along with his partners, who are known as cangaceiro, and who lived under his laws. That worked as a respect sign and served to diminish the possible sufferings of the soul that could float over them. Then, the question of religiosity inside the cangaço turns into a fundamental thing to enrich the thematic in which, now and then, the interested ones would have to face with new works. However, they do not mention exclusively the question of the religious life of the group or as known the gang. many works about the cangaço have been published, and especially about Lampião, being one more this essay was written with the purpose of contributing with the expanding of the view about the cangaço phenomenon, in special using the elements of the Religious Sciences to understand a little more about the religious life of Lampíão and also of his partners, the cangaceiros who lived under his orbit and command.